Presentación - Kaplan, Carina Viviana (2024)
The Education, Sensibilities and Social Justice dossier brings together a set of works by international academics who build relevant arguments about the role of affectivity in the constitution of the social bond. The theoretical and empirical contributions can be framed in the affective turn of the field of educational research. Affectivity is no longer interpreted as a refuge of intimacy and becomes an object of public projection. Emotions constitute a backbone of social justice to the extent that “they are endowed with a vital force that opens futures” (Ahmed, 2015, p.304). The integral perspective on emotional ties conceives them as links that unite society (Elías, 1998). By assuming a relational epistemological horizon, affect is interpreted as an interwoven expression of the material and the subjective. Topics related to the processes of socialization and subjectivation, power relations and resistance practices carried out by actors in the educational community are addressed.